2009
DOI: 10.1590/s0100-40422009000600020
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity of eugenol derivatives

Abstract: Recebido em 3/7/08; aceito em 14/1/09; publicado na web em 28/7/09 Toxicity and antioxidant capacity of eugenol derivatives (E2 = 2-Methoxy-4-[1-propenylphenyl]acetate, E3 = 4-Allyl-2-methoxyphenylacetate, E4 = 4-Allyl-2-methoxy-4-nitrophenol, E5 = 5-Allyl-3-nitrobenzene-1,2-diol, E6 = 4-Allyl-2-methoxy-5-nitrophenyl acetate) were evaluated in order to determine the influence of the sustituents. E2-E6 were synthesized from eugenol (E1). E1 was extracted from cloves oil, and E2-E6 were obtained through acetylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 13 publications
2
36
1
3
Order By: Relevance
“…Structural differences or the ratio of the compounds to each other may account for the differences. Hidalgo et al (2009) studied the effect of donating electrons from eugenol derivatives; their results support our findings. They found that two eugenol derivatives displayed higher ORAC values due to their ability to stabilize the radical in the ortho (o) and para (p) positions of an aromatic ring.…”
Section: Oracsupporting
confidence: 79%
“…Structural differences or the ratio of the compounds to each other may account for the differences. Hidalgo et al (2009) studied the effect of donating electrons from eugenol derivatives; their results support our findings. They found that two eugenol derivatives displayed higher ORAC values due to their ability to stabilize the radical in the ortho (o) and para (p) positions of an aromatic ring.…”
Section: Oracsupporting
confidence: 79%
“…Miranda, Cardoso, Batista, Rodrigues, & Figueiredo (2016) The high values for the antioxidant activities presented by BHT and the low values presented by the essential oil can be explained by the fact that the reduction of DPPH occurs via transfer of a hydrogen atom or a mechanism of electron transfer from the antioxidant compound. In general, the constituents of the essential oil did not resemble the phenolic structure of BHT, which can donate the hydrogen atom of the hydroxyl group to form a phenol radical that can be stabilized by resonance with the double bonds of the aromatic ring (Hidalgo et al, 2009). Besides, terpenes show low solubility in the reaction medium of the assay, because this test utilizes methanol or ethanol as solvent.…”
Section: Antioxidant Activitymentioning
confidence: 97%
“…Eugenol derivatives exhibited a haemolysis percentage lower than 1%, which indicate very low toxicity for red blood cell membranes. 3 In vitro studies carried out on two human cancer cell lines: DU-145 (androgen-insensitive prostate cancer cells) and KB (oral squamous carcinoma cells) measuring cell viability by the tetrazolium salt assay. Lactic dehydrogenase (LDH) release was also measured to evaluate cell toxicity as a result of cell disruption, subsequent to membrane rupture.…”
Section: Introductionmentioning
confidence: 99%
“…Safrole (1) and its synthetic derivatives (2)(3)(4)(5)(6)(7)(8) were tested in vitro for antiproliferative effect on two human tumor breast cancer cell lines (MDA-MB-231, MCF-7), one human colorectal cancer cell line (DLD-1) and one dermal human fibroblast cell line (DHF). The in vitro growth inhibition assay used was based on sulphorhodamine dye, widely used to quantify cell viability.…”
Section: Introductionmentioning
confidence: 99%